¿Vivir entre dos mundos? Parentesco y política en la vida de José Valdebenito, “Encargado de los Indios” en Cruz de Guerra (1830-1859) - Luciano Literas (Corpus: Archivos Virtuales de la Alteridad Americana, 2014)
This article analyzes the cultural brokers role as well as the intersections of the Indigenous agency and state policies in the Indian frontier during the nineteenth century in Argentina, in the political and military life of José Valdebenito. After fighting against the Chilean republicans during the war to the death (1819-1832), Valdebenito migrated to the Pampa with the Borogas, where they negotiated the peace with the government of Buenos Aires (1830). Valdebenito joined the army of Buenos Aires and was a lenguaraz (interpreter) for the Boroga chiefs (caciques). After that he advocated for the Boroga settling in Cruz de Guerra (Veinticinco de Mayo, Buenos Aires) under state jurisdiction, where he commanded Indigenous and Creole soldiers for more than 20 years until his death in 1859. These services and his kinship with the descendants of the chief Rondeau granted him a higher position in the local hierarchy and a significant leadership over the Borogas, to the point of being essential to explain the advance of the state frontiers in Veinticinco de Mayo.